2007
DOI: 10.1128/jvi.00243-07
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Reactivation of Herpes Simplex Virus Type 1 in Latently Infected Murine Sensory Ganglia

Abstract: Careful studies of mouse trigeminal ganglia (TG) latently infected with herpes simplex virus type 1 (HSV-1) indicate the presence of productive cycle viral gene products and persistent immune response, suggesting ongoing spontaneous viral reactivation in these tissues. In the present study we set out to determine whether infectious virus is present in murine TG latently infected with HSV-1 (KOS). At 37 days after ocular inoculation we found a small amount of infectious virus in ca. 6% of latently infected muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 39 publications
4
61
0
Order By: Relevance
“…Although infection was controlled in DRG xenografts, the frequency of HSV-1 infection of human neurons, judged by HSV-1 protein and LAT expression, was significantly higher at 8 weeks after DRG inoculation than has been observed in murine models of HSV-1 ganglion infection after footpad or ocular inoculation, even when using the attenuated R8411 strain. In the ocular model, mice that survive have no apparent replicating virus in DRG or trigeminal ganglia four to six weeks after infection (10,36,40,41). However, the frequency of infected ganglion cells in murine models is much lower than the estimate of 2 to 10.5% from human autopsy studies (42).…”
Section: Discussionmentioning
confidence: 76%
“…Although infection was controlled in DRG xenografts, the frequency of HSV-1 infection of human neurons, judged by HSV-1 protein and LAT expression, was significantly higher at 8 weeks after DRG inoculation than has been observed in murine models of HSV-1 ganglion infection after footpad or ocular inoculation, even when using the attenuated R8411 strain. In the ocular model, mice that survive have no apparent replicating virus in DRG or trigeminal ganglia four to six weeks after infection (10,36,40,41). However, the frequency of infected ganglion cells in murine models is much lower than the estimate of 2 to 10.5% from human autopsy studies (42).…”
Section: Discussionmentioning
confidence: 76%
“…Recent studies have shown that T cell exhaustion occurred as a result of chronic infection with several different viruses (3,8,30) and that the presence of low-level viral antigen during chronic/latent infection leads to T cell exhaustion (42). HSV-1 latency was originally thought to be a completely dormant situation with no viral gene expression, but recent studies have shown that this is not the case (11,31,34). Thus, to investigate potential differences in the TG from gK-, gD-, and mock-immunized mice, we performed qRT-PCR analysis on the same TG used above to determine the expression levels of mRNAs characteristic of T cells (CD4, CD8) and exhaustion markers (PD-1, Tim-3).…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly used animal model of HSK is mice. However, in contrast to HSV-1-infected humans or rabbits, spontaneous virus reactivation in mice is rare (45). The evidence generated using the mouse model suggests that eye disease may be associated with immune responses triggered by the virus, rather than the virus directly.…”
Section: Discussionmentioning
confidence: 99%